2021
DOI: 10.1002/acm2.13440
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application and improvement of a CNN‐based autosegmentation model for clinical target volumes in cervical cancer radiotherapy

Abstract: Objective: Clinical target volume (CTV) autosegmentation for cervical cancer is desirable for radiation therapy. Data heterogeneity and interobserver variability (IOV) limit the clinical adaptability of such methods. The adaptive method is proposed to improve the adaptability of CNN-based autosegmentation of CTV contours in cervical cancer. Methods: This study included 400 cervical cancer treatment planning cases with CTV delineated by radiation oncologists from three hospitals. The datasets were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In recent years, deep learning-based image processing methods have been widely applied to the field of medical imaging, including medical image segmentation ( 7 9 ), disease diagnosis ( 10 , 11 ), medical image denoising ( 12 ), and medical image translation ( 13 , 14 ). The development of deep learning technology has accelerated the process of clinical treatment and improved the mining of medical image information.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, deep learning-based image processing methods have been widely applied to the field of medical imaging, including medical image segmentation ( 7 9 ), disease diagnosis ( 10 , 11 ), medical image denoising ( 12 ), and medical image translation ( 13 , 14 ). The development of deep learning technology has accelerated the process of clinical treatment and improved the mining of medical image information.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Researchers have conducted segmentation of soft tissue organs on CT and/or CBCT using neural encoding/decoding based on the CNN architecture, thereby exploiting supervised training. [13][14][15][16][17][18][19][20][21] The main requirement for this type of approach is anatomical correspondence between the input image (CT or CBCT), and the ground truth reference label. [13][14][15][16][17][18][19][20][21] Although CNNbased segmentation works well for full field of view (FOV) CBCT, [13][14][15][16][17]20,21 it is unknown whether CNNbased segmentation using limited FOV CBCT is possible.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple investigators have reported that atlas‐based and convolutional neural network (CNN)‐based segmentation was successfully applied to CT and CBCT images, showing that the CNN‐based methods can provide greater segmentation accuracy and better efficiency than atlas‐based methods 10–12 . Researchers have conducted segmentation of soft tissue organs on CT and/or CBCT using neural encoding/decoding based on the CNN architecture, thereby exploiting supervised training 13–21 . The main requirement for this type of approach is anatomical correspondence between the input image (CT or CBCT), and the ground truth reference label 13–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Although CNN-based segmentation is becoming more widely adopted in some radiotherapy workflows (Schreier et al 2020, Cha et al 2021, Chang et al 2021, it is not widely used in settings aiming to assess response to therapy in patients with advanced cancers. In addition, a number of uncertainties and unknowns remain to be sufficiently addressed.…”
Section: Introductionmentioning
confidence: 99%